Nicotine Replacement Combined with a Novel Compound (ProBAN) for Smoking Cessation: A Pilot Study - Richard Leigh; Norman M Viner; Gerard Cox; Jeffrey W Balon; Douglas MC Wilson; Denise O’Shaughnessy; Corinne Walker; Gerry Brosky; Malcolm R Sears (Canadian Respiratory Journal)
BACKGROUND: Smoking cessation rates with available pharmacological therapies remain suboptimal. Anecdotal observations with a combination of sublingual pralidoxime and ipratropium (ProBAN) suggested that these agents in combination with nicotine gum improved quit rates.